First Experience With the Synergy Micro‐Pump in Patients in INTERMACS Class 1–2 as a Bridge to Transplantation: Pushing the Limits?. Issue 2 (20th May 2014) - Sabashnikov, Anton; Popov, Aron‐Frederik; Bowles, Christopher T.; Weymann, Alexander; Mohite, Prashant N.; Wahlers, Thorsten; Wittwer, Thorsten; Zych, Bartlomiej; Garcia‐Saez, Diana; Patil, Nikhil P.; Fatullayev, Javid; Amrani, Mohamed; et al.
Abstract The Synergy Micro‐pump is the smallest implantable left ventricular assist device (LVAD) and provides partial flow support up to 4.25 L/min. It was shown that early intervention with this device can provide substantial benefits to patients with severe heart failure not yet sick enough for a full‐support LVAD. However, as it can be inserted via small incisions with no need for sternotomy or cardiopulmonary bypass, it might be beneficial for selected high‐risk patients. The aim of this study was to evaluate the efficacy of the Synergy Micro‐pump in patients in INTERMACS class 1–2. From February 2012 to August 2013, 13 patients with severe heart failure were supported with the Synergy Pocket Micro‐pump. Patients were divided into two groups according to INTERMACS class: the high‐risk group (INTERMACS class 1–2) and the low‐risk group (INTERMACS class 3–4). There were seven patients in INTERMACS class 1–2 and six in INTERMACS class 3–4. Patient demographics, perioperative characteristics, and postoperative outcomes were compared. There were no statistically significant differences in patient demographics, and mean support time was 108 ± 114 days in the high‐risk group and 238 ± 198 days in the low‐risk group. Also, there were no significant differences in perioperative characteristics or in the rate of postoperative adverse events. The overall survival was comparable between the two groups (one late death in each group, log‐rank P = 0.608). Two patients from the high‐risk group were upgraded to a full‐support LVAD (P = 0.462) after 65 ± 84.9 days of mean support. One patient from the high‐risk group and two patients from the low‐risk group were successfully transplanted (P = 0.559). The use of the Synergy Micro‐pump in INTERMACS 1–2 patients is feasible and is associated with similar postoperative outcome as in patients in INTERMACS 3–4. Carefully selected patients with severe heart failure could benefit due to the small size of the pump; however, further studies and medium‐term follow‐up are required.